O cenário atual da tecnologia Bim em empresas de arquitetura, engenharia e construção: um estudo de caso na cidade de Pau dos Ferros - RN - Castro, Antonio Carlos Gardel de Freitas (Universidade Federal Rural do Semi-Árido, 2019)
Being the Civil Construction sector a segment that is directly linked to the economic situation of a country, it is essential that there is a high level in the quality of management and development of the activities of this sector, in order to reduce waste. With this, the modeling of construction with information or BIM, is a methodology has been growing a lot, because it brings benefits such as collaboration between work fronts, simulations of time and cost of a work and the compatibility of the project disciplines, so, allows greater reliability and safety in the results obtained. The present work seeks to study the use of this technology in the Architecture, Engineering and Construction companies of the city of Pau dos Ferros - RN, and for this a data collection was carried out in eight of these companies, as well as a theoretical revision on the subject. As a result, it was noticed that the use of BIM is still in the initial phase and the lack of adequate qualification, high value of the software and the resistance of the team to method transition are the main barriers faced for its implementation. Therefore, the importance of introducing BIM in the activities of these companies is stressed both by the compulsory nature as of 2021 and by all the benefits presented in this work.
Keywords: Construção Civil; BIM; Compatibilização; Civil Construction; Compatibility; ENGENHARIAS::ENGENHARIA CIVIL